Issues and Challenges in Testing and Assessment Practices among Public Schools: Basis for Policy Enhancement (Journal of Informatics Education and Research, 2025)
This study focused on the issues and challenges of testing and assessment practices among public schools in the Schools Division of Olongapo City as the baseline of policy enhancement. Qualitative research was employed in explaining the issues and challenges of testing and assessment during this new normal. As to methodology, Situational Analysis was used in this study which comprised three phases namely looking inward, looking outward, and looking forward. Data were collected using Key Informant Interview (KII) and Focus Group Discussion (FGD).Findings revealed that on testing practices, teachers were assigned additional tasks which could have affected the quality of the test. Learners were also affected by the timeliness of receiving and retrieving modules. Delays of module delivery had also an impact on the testing process including the parents or guardians who had a strong influence on their children's responses which may have affected the validity of the test. The interventions at home and the presumption of copying or cheating have somehow affected the test results. Further, assessment issues also showed learners having difficulty answering the test due to a lack of comprehension, hence, teachers also struggled in grading because the data collected may not be reliable. With such findings, there are issues to be discussed in schools regarding test quality assurance.The study recommended that the policy may be enhanced by using adjectival ratings because in modular learning modality, reliability and validity are issues. It is also suggested that all students receive one-on-one evaluations at the end of the school year to have a more objective system in grading their learned competencies.